THE DIFFERENCES BETWEEN THE 2013 CURRICULUM AND THE MERDEKA CURRICULUM: TEACHER’S UNDERSTANDING - Afgany, Dea Marwah; Fajriah, Yustika Nur; Nursalam, Hafidatun; Soni, Mohammad (IPI Garut Press, 2023)
Curriculum change is conducted as an effort to raise the standard of education. In Indonesia context, the education curriculum has been shifted from the 2013 Curriculum to the Merdeka Curriculum. This change brings out some pros and cons in which some teachers support this alteration, meanwhile, others say no to this change. In response to that claim, this research aimed to analyze the differences between the 2013 Curriculum and the Merdeka Curriculum from the teacher’s understanding. To achieve that goal this qualitative research was conducted through the use of semi- structured interviews as the data collection. The data were collected from an English teacher in one of the senior high schools in Garut, West Java. The result showed that the respondent has quite understood the difference between the 2013 curriculum and the Merdeka curriculum in the aspect of the general characteristics of the curriculum and the learning method used. Even the findings revealed that understanding of the curriculum can be captured more for the Merdeka curriculum than the 2013 curriculum, meaning that there are many aspects of the 2013 curriculum that the teacher has implemented but she still does not fully understand. In spite of these findings, the teacher claims that there are challenges such as insufficient infrastructure or supporting factors of facilities to help her in conducting the Merdeka curriculum